Key problem: transportation of panary resources (to history of building of railways on Ukrainian earths) - H. I. Hlazunov (History of science and technology, 2013)
In the article the problem of transportation of panary resources per rail is illuminated on territory of Ukraine (second half of ХІХ - нач ХХ of centuries).